A relative analysis to cascaded fractional-order controllers in microgrid non-minimum phase converters using EHO - Asmy, N. R. Anisha; Ramprabhakar, J.; Anand, R.; Meena, V. P.; Jadoun, Vinay Kumar (Scientific reports, 2025)
Microgrids integrate various distributed energy resources to enhance energy reliability and sustainability. Power electronic converters are vital in microgrids since they provide efficient, reliable, and flexible operation. There are numerous controllers available that can be applied to these converters, and lately, fractional-order controllers (FOC) have gathered huge recognition. These controllers provide enhanced flexibility and superior performance in managing dynamic behavior. There are various structures of FOCs, and this article predominantly focuses on comparing different cascaded fractional order controllers (C-FOC). Four distinct topologies of cascaded fractional order proportional integral (C-FOPI) controllers are selected for comparison with one another and with the cascaded proportional integral controller used in a non-minimum phase converter, such as the boost converter employed in a microgrid system. The controllers are optimized using the Elephant Herd Optimization (EHO) algorithm with the Integral of Time-weighted Absolute Error (ITAE) serving as the performance metric. Each controller is subject to variation in system changes, and the outcomes are documented and correlated to ascertain the optimum structure. The simulation outcomes endorsed notable advancements in terms of transient and steady-state performance, featuring improved resilience to parameter changes, a reduction of 36.6% in settling time, 15% in overshoot, 20.1% in rise time, an improved phase margin of more than 51% and more than 50% reduction in performance indices compared to traditional cascaded proportional integral controllers (PI-PI).